2017
DOI: 10.1016/j.cej.2016.10.127
|View full text |Cite
|
Sign up to set email alerts
|

Composite ultrafiltration membrane tailored by MOF@GO with highly improved water purification performance

Abstract: Developing advanced filtration membrane with high flux, good solute rejection and excellent antifouling performance is highly demanded. Hydrophilic graphene oxide (GO) nanosheets are attractive fillers for the preparation of composite membranes for water purification. However, strategies that can fully exploit the advantages and remedy the drawbacks of GO nanosheets are still needed. In this work, UiO-66 was specifically anchored to the GO layers as a porous modifier. The incorporated UiO-66 can effectively pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(128 citation statements)
references
References 34 publications
5
119
0
Order By: Relevance
“…As we all know, water is one of the most important substances in human's lives, so water quality has a great effect on the health of humans . Nevertheless, because of the expansion of industrial factories and a rapidly increasing population, more and more contaminants are poured into environmental water, threatening the lives of humans and wildlife.…”
Section: Water Purificationmentioning
confidence: 99%
See 2 more Smart Citations
“…As we all know, water is one of the most important substances in human's lives, so water quality has a great effect on the health of humans . Nevertheless, because of the expansion of industrial factories and a rapidly increasing population, more and more contaminants are poured into environmental water, threatening the lives of humans and wildlife.…”
Section: Water Purificationmentioning
confidence: 99%
“…Currently, dye wastewater pollution is becoming an increasingly frightening threat to human beings . The following paragraphs review the published reports regarding the adsorption performance of MOF/graphene‐based materials for some main dye pollutants including methyl orange (MO), rhodamine B (RhB), malachite green (MG), direct red (DR), methylene blue (MB), and Congo red (CR).…”
Section: Water Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…30 After UiO-66 modification by TG, all diffractions belong to UiO-66 were well preserved, indicating that the presence of TG did not disturb the formation of crystals of UiO-66. [35][36][37] Notably, the broadened diffraction peaks indicated that T on the surface of GO (in the TG@UiO-66 matrix) has a low degree of crystallinity. 38 Furthermore, the absence of GO diffraction is due to the insertion of UiO-66 between TG layers that effectively reduces the van der Waals binding energy between the GO sheets and improves the layer exfoliation and also high dispersion of TG layers during the nanocomposite preparation can be another reason for this observation.…”
Section: Njc Papermentioning
confidence: 99%
“…17 Thus, researchers focused on GO and metal-organic framework (MOF) nanocomposites. [18][19][20][21] As a network-like compound with the advantages of an adjustable structure, high porosity and large specic surface area, 22 MOF is constructed by combining a metal center and organic linkers via coordination bonds. The ultra-high specic surface area provides MOF with excellent adsorption properties for gas separation and storage, but weak dispersion forces attract small molecules, limiting the practical applications.…”
Section: Introductionmentioning
confidence: 99%